Common delivery systems for enhancing in vivo bioavailability and biological efficacy of nutraceuticals - Yuwen Ting; Yike Jiang; Chi-Tang Ho; Qingrong Huang (Journal of Functional Foods, 2014)
Nutraceuticals are an emerging food category defined as dietary elements which can provide health benefits beyond the basic nutritional values. As more compounds have been identified to provide biological benefits, their efficacies are often limited due to insufficient dose efficiency after oral administration. Starting from the mouth, nutraceuticals begin their journey through the gastrointestinal (GI) tract where they are subjected to various physiochemical transformations, from which they may lose their bioactivities completely. To improve the oral efficacy, many edible delivery systems have been developed to enhance the bioavailability of nutraceuticals through various mechanisms. In this article, we first provide a brief overview on biological fate of nutraceuticals in various segments within human GI tract and possible strategies to overcome factors that lead to low bioavailability. A literature review which confirmed the usefulness of different delivery systems to enhance the in vivo oral bioavailability and efficacy of nutraceuticals was also provided.